ANTIMICROBIAL POTENTIALS OF SOIL FUNGI METABOLITES, MOLECULAR DYNAMICS AND THEIR 3D PROTEIN STRUCTURAL PREDICTION USING BIOINFORMATICS TOOL - O. N., MAJOLAGBE; D. A., AINA; I. O., OMOMOWO; A., THOMAS (International Journal of Current Pharmaceutical Research, 2020)
Objective: To determine the antimicrobial potentials of secondary metabolite of soil fungi and predict their 3D structure and molecular identity. Methods: Pure soil fungi were isolated from soil samples and cultured under submerged fermentation (Smf) for their metabolites using Potato Dextrose Agar and Broth. The secondary metabolites of the isolated fungi were obtained intracellularly after 21 d of incubation in a rotary shaker incubator. The antimicrobial potentials of the metabolites were investigated against four (4) clinical isolates, namely: Staphylococcus aureus, Klebsiella spp, Candida albicans and Escherichia coli. These soil fungi were further characterized to the molecular level and their evolutionary relationships established using bioinformatics tools. Protein structure of each of the fungi isolates was predicted using PHYRE-2. Results: Out of all the soil fungi isolated, the metabolite of Aspergillus aculeatus showed the highest antimicrobial activities against Staphylococcus aureus (23.00±2.34 mm), Escherichia coli (9.00±1.44 mm) and Klebsiella spp (24.00±3.45 mm). The 3D protein structure predicted showed that each of the organisms consists of different amino-acid compositions such as: serine, tyrosine, proline, arginine, glycine, phenylalanine leucine with other notable biological properties. Conclusion: The work revealed that secondary metabolites of the isolated fungi carry an important role in combating infectious agents thereby, providing roadmaps for the biosynthesis of many synthetic and semi-synthetic drugs and bio-products which are environmentally friendly.